The Spectrum of ELANE Mutations and their Implications in Severe Congenital and Cyclic Neutropenia. Issue 6 (2nd April 2013) - Germeshausen, Manuela; Deerberg, Sabine; Peter, Yvonne; Reimer, Christina; Kratz, Christian P.; Ballmaier, Matthias
<x xml:space="preserve">Abstract</x> We analyzed the spectrum of ELANE mutations, which are responsible for the majority of cases of severe congenital neutropenia (CN) and cyclic neutropenia (CyN). Using predictive algorithms we found a trend for a more benign prediction of CyN‐associated mutations compared to those associated with CN. Within the group of CN the course of disease was more severe in patients with ELANE mutation compared to patients without ELANE mutations. The predictive value of specific ELANE mutations for leukemogenesis was low. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>